mRNA expression of diacylglycerol kinase isoforms in insulin-sensitive tissues: effects of obesity and insulin resistance - Mannerås-Holm, Louise (Physiol Rep, 2015)
Diacylglycerol kinase (DGK) isoforms regulate signal transduction and lipid metabolism. DGKδ deficiency leads to hyperglycemia, peripheral insulin resistance, and metabolic inflexibility. Thus, dysregulation of other DGK isoforms may play a role in metabolic dysfunction. We investigated DGK isoform mRNA expression in extensor digitorum longus (EDL) and soleus muscle, liver as well as subcutaneous and epididymal adipose tissue in C57BL/6J mice and obese and insulin-resistant ob/ob mice. All DGK isoforms, except for DGKκ, were detectable, although with varying mRNA expression. Liver DGK expression was generally lowest, with several isoforms undetectable. In soleus muscle, subcutaneous and epididymal adipose tissue, DGKδ was the most abundant isoform. In EDL muscle, DGKα and DGKζ were the most abundant isoforms. In liver, DGKζ was the most abundant isoform. Comparing obese insulin-resistant ob/ob mice to lean C57BL/6J mice, DGKβ, DGKι, and DGKθ were increased and DGKε expression was decreased in EDL muscle, while DGKβ, DGKη and DGKθ were decreased and DGKδ and DGKι were increased in soleus muscle. In liver, DGKδ and DGKζ expression was increased in ob/ob mice. DGKη was increased in subcutaneous fat, while DGKζ was increased and DGKβ, DGKδ, DGKη and DGKε were decreased in epididymal fat from ob/ob mice. In both adipose tissue depots, DGKα and DGKγ were decreased and DGKι was increased in ob/ob mice. In conclusion, DGK mRNA expression is altered in an isoform- and tissue-dependent manner in obese insulin-resistant ob/ob mice. DGK isoforms likely have divergent functional roles in distinct tissues, which may contribute to metabolic dysfunction.